POTENSI DAUN SAMBILOTO (Andrographis paniculata) SEBAGAI NATURAL FEED ADDITIVE TERHADAP PERFORMA BROILER - Maulana Azka Mahogra; Nurul Humaidah (BUANA SAINS, 2026)
Andrographis paniculata (sambiloto), with its active compound, andrographolide, shows potential as a feed additive to enhance broiler chicken performance. This study aimed to evaluate the potential of Sambiloto as a natural feed additive on broiler performance. The materials used included 50 male broilers aged 14 days, commercial feed, and Sambiloto powder. The research employed an experimental method with a Completely Randomized Design (CRD). There were 5 treatments, each replicated 4 times: P0 (negative control without Sambiloto), P1 (positive control with vitamins without Sambiloto), P2 (5% Sambiloto), P3 (10% Sambiloto), and P4 (15% Sambiloto). Treatments were administered for 21 days. The observed variables were production performance, including final body weight, feed conversion ratio (FCR), livability percentage, and performance index (PI). Data were analyzed using Analysis of Variance (ANOVA) followed by Least Significant Difference (LSD) to determine differences between treatments. Research results showed that supplementing sambiloto in feed had a highly significant effect (P0,01) on final body weight and the PI of broilers, but no significant effect (P0,05) on the FCR and percentage of live chickens. The highest average final body weight was observed in the control group at 1.6 kg. The highest average PI was found in the 5% sambiloto treatment at 613.11. The best average FCR was recorded in the 5% sambiloto treatment at 1.20. The highest average percentage of live chickens (100%) was achieved in the control, 5% sambiloto, and 10% sambiloto groups. In conclusion, Sambiloto leaves have the potential to enhance broiler performance.